PENGARUH MEDIA PEMBELAJARAN VISUAL DENGAN BANTUAN MICROSOFT POWERPOINT TEHADAP MOTIVASI BELAJAR DALAM PELAJARAN PPKn SISWA KELAS XI DI SMA NEGERI 4 DUMAI - Miswanti, Weni; Gimin, Gimin; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : his study aims to determine the effect of visual learning media with the help of Microsoft Powerpoint on motivation to learn in PPKn lessons at SMA 4 Dumai. This research is motivated by the low motivation of learning PPKn students of SMA 4 Dumai. This research is an experimental descriptive quantitative. The population in this study were students of class XI IPS SMA 4 Dumai, while the sample in this study were students of class XI IPS 2 (experimental class) and class XI IPS 1 (control class) taken randomly. Then the data were analyzed using t-test tests showing that there was an effect of visual learning media with the help of Microsoft powerpoint at Dumai Public High School 4. (t_ (count = 24.55>) ttable = 1.99) Where there is an increase in the average PPKn learning motivation of the experimental class from 20.14 to 25.62 and the average PPKn learning motivation of the control class from 20.55 to 20 , 72. With Ngain's contribution of 0.36 in the